Overexpression of peptidase inhibitor 16 attenuates angiotensin II–induced cardiac fibrosis via regulating HDAC1 of cardiac fibroblasts. Issue 9 (30th March 2020) - Deng, Mengqing; Yang, Shuo; Ji, Yue; Lu, Yan; Qiu, Ming; Sheng, Yanhui; Sun, Wei; Kong, Xiangqing
Abstract: Cardiac hypertrophy and fibrosis are the major causes of heart failure due to non‐ischaemia heart disease. To date, no specific therapy exists for cardiac fibrosis due to the largely unknown mechanisms of disease and lack of applicable therapeutic targets. In this study, we aimed to explore the role and associated mechanism of peptidase inhibitor 16 (PI16) in cardiac fibrosis induced by angiotensin II. In cardiac fibroblasts (CFs), overexpressed PI16 significantly inhibited CF proliferation and the levels of fibrosis‐associated proteins. Further analysis of epigenetic changes in CF revealed that overexpressed PI16 decreases the nuclear level of histone deacetylase 1 (HDAC1) after angiotensin II treatment, resulting in increased histone 3 acetylation in K18 and K27 lysine. However, overexpression of HDAC1 by an adenovirus vector in CFs reversed these changes. Echocardiography showed that PI16 transgenic (Tg) mice have smaller left ventricle mass than wild‐type mice. Histological analysis data showed that PI16 Tg mice demonstrated smaller cardiomyocyte size and less collagen deposition than wild‐type mice. The effects of PI16 on HDAC1 and histone 3 were also confirmed in PI16 Tg mice using immunostaining. Generally, PI16 is a HDAC1 regulator specifically in CFs, and PI16 overexpression prevents cardiac hypertrophy and fibrosis by inhibiting stress‐induced CF activation.